2007
DOI: 10.1677/joe-07-0097
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositide 3-kinases as a common platform for multi-hormone signaling

Abstract: In multicellular organisms, concerted actions of different tissues are regulated inside single cells by signal transduction mechanisms that, subsequently to hormones sensing, trigger intracellular responses. In recent years, increasing evidence indicates phosphoinositide 3-kinases (PI3K) as crucial signal transducing elements that regulate communication across the plasma membrane. PI3K generate lipid secondary messengers that trigger a plethora of intracellular responses ranging from metabolic regulation to ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
128
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(134 citation statements)
references
References 125 publications
(120 reference statements)
3
128
0
3
Order By: Relevance
“…a p < 0.001, effect of the absence of ob gene. *p < 0.05, **p < 0.01 vs WT mice; # p < 0.05, ## p < 0.01 vs ob/ob mice The activation of the PI3K/Akt transduction signaling is necessary for leptin-induced macrophage migration 52 and proinflammatory cytokine production 55 in several cell types 46,56 . In this regard, we found that the covalent, irreversible inhibitor of PI3K, wortmannin 57 , decreased Tnc gene expression levels in differentiated 3T3-L1 adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…a p < 0.001, effect of the absence of ob gene. *p < 0.05, **p < 0.01 vs WT mice; # p < 0.05, ## p < 0.01 vs ob/ob mice The activation of the PI3K/Akt transduction signaling is necessary for leptin-induced macrophage migration 52 and proinflammatory cytokine production 55 in several cell types 46,56 . In this regard, we found that the covalent, irreversible inhibitor of PI3K, wortmannin 57 , decreased Tnc gene expression levels in differentiated 3T3-L1 adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K family consists of multiple members (Andrews et al, 2007;Hirsch et al, 2007). Each PI3 kinase has a catalytic domain of 110 kDa, named p110.…”
Section: Pkc Kinase Activity Is Required For A-p Guidance Of Commissumentioning
confidence: 99%
“…We hypothesized that the altered SL profile might preferentially affect the PI3K pathway (Hirsch et al ., 2007; Silva et al ., 2012). It was shown that levels of phosphorylated p85 (p‐p85) were higher in the GSM of young (25 weeks old) CerS2‐null mice (upper panel of Fig.…”
Section: Resultsmentioning
confidence: 99%